Identification of Potential and Challenges of MSMEs in Bintan Regency: A Case Study of Pengudang Village, Bintan Regency, Kepulauan Riau - Febri Ardiana Zingga; Dea Dwi Agustin; R.Nuzul Fazly; Nikodemus Niko (Master Program in Sociology, Faculty of Social and Political Sciences, Universitas Sriwijay, 2024)
This study aims to identify the conditions of Micro, Small, and Medium Enterprises (MSMEs) in Pengudang Village using a SWOT analysis approach. MSMEs play a vital role in supporting the local economy and creating employment opportunities for the village community; however, their sustainability is often challenged by various internal and external factors. Employing a qualitative method and in-depth interview techniques, data were collected from MSME owners and relevant stakeholders. SWOT analysis was used to identify the strengths, weaknesses, opportunities, and threats affecting the development of MSMEs in this area. The findings reveal that MSMEs in Pengudang Village benefit from strengths such as access to local resources, including raw materials and labor, as well as support from the local community. However, weaknesses in access to capital, technology, and managerial skills remain significant obstacles. Opportunities arise from the growth of local tourism and demand for local products, yet threats emerge from intense competition with products from outside the region and limited infrastructure. Based on these findings, the study recommends efforts to enhance capacity and provide sustained support from the government and related institutions to strengthen the competitiveness of MSMEs in Pengudang Village.